2016
DOI: 10.1002/cjg2.20211
|View full text |Cite
|
Sign up to set email alerts
|

Investigations and Experiments of Variances Filtering Technology in the Ensemble Data Assimilation

Abstract: An experimental Ensemble Data Assimilation (YH‐EDA) system has been built with 10 ensemble members based on the operational YH4DVAR system. The system can provide flow‐dependent background‐error variances, which are superior to the operational ones both in structure and magnitude. However, the finite ensemble size implies a detrimental sampling noise for the variances estimation. To solve this problem, a spectral filtering technique is implemented to formulate a low‐passing filter. Taking into account the typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Bonavita, et al [39] showed that a relatively small set (e.g., 10 members) can adequately characterize the large-scale error structure of extratropical cyclones, and a larger set can model more refined features. The research of Liu, et al [40] found that the variance estimation using 10 members is very similar to the 30 members except for the relative reduction in noise, and there is no essential difference between the two. The number of EDA members in this article is also taken as 10.…”
Section: Flow-dependent Estimation and Postprocessing Of Variancesmentioning
confidence: 88%
“…Bonavita, et al [39] showed that a relatively small set (e.g., 10 members) can adequately characterize the large-scale error structure of extratropical cyclones, and a larger set can model more refined features. The research of Liu, et al [40] found that the variance estimation using 10 members is very similar to the 30 members except for the relative reduction in noise, and there is no essential difference between the two. The number of EDA members in this article is also taken as 10.…”
Section: Flow-dependent Estimation and Postprocessing Of Variancesmentioning
confidence: 88%
“…e YH4DVAR system is an operational deterministic 4D-Var system that uses the global spectral model as a constraint to impose a dynamic balance on the assimilation [17]. Considering that the sampling noise introduced by the randomization technique has a negative effect on the estimate, a spectral filtering method truncated at a fixed wavenumber in an operational setting solves the issue of sampling noise in the YH4DVAR system [18]. e spectral filtering method enables the removal of most of the sampling noise while preserving the standard deviations of interest.…”
Section: Introductionmentioning
confidence: 99%